A Novel Direct Torque Control for Induction Machine Drive System with Low Torque And Flux Ripples using XSG - Souha Boukadida; Soufien Gdaim; Abdellatif Mtibaa (Institute of Advanced Engineering and Science, 2014)
The conventional Direct Torque Control (DTC) is known to produce a quick and robust response in AC drives. However, during steady state, stator flux and electromagnetic torque which results in incorrect speed estimations and acoustical noise. A modified Direct Torque Control (DTC) by using Space Vector Modulation (DTC-SVM) for induction machine is proposed in this paper. Using this control strategy, the ripples introduced in torque and flux are reduced. This paper presents a novel approach to design and implementation of a high perfromane torque control (DTC-SVM) of induction machine using Field Programmable gate array (FPGA).The performance of the proposed control scheme is evaluated through digital simulation using Matlaband Xilinx System Generator. The simulation results are used to verify the effectiveness of the proposed control strategy.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6374